Healthcare workers' perceptions and experiences of implementing voluntary medical male circumcision in KwaZulu-Natal, South Africa - Celenkosini T. Nxumalo; Gugu G. Mchunu (AOSIS, 2020)
Background: Voluntary Medical Male Circumcision (VMMC) is an effective HIV prevention strategy prioritized by the World Health Organisation (WHO) for regions of high HIV prevalence, South Africa (SA) and in particular KwaZulu-Natal (KZN) is one of such regions. Since the roll out of VMMC in 2010 there has been little research conducted on the implementation of this service. Existing studies on the uptake of VMMC have mainly focused on service users resulting in a paucity of data on health care workers perspectives on the intervention. Aim: To analyse health care workers' perceptions and experiences of implementing voluntary medical male circumcision in KZN, SA. Setting: The study took place at six different health districts and their six respective rural clinics in the KZN province of SA. Methods: A qualitative approach using a phenomenographic design was employed. Data were collected from a sample of 18 participants comprising of health care providers (n = 12) and health policy makers (n = 6). Individual, face-to-face interviews were conducted using a semi-structured interview guide. An audiotape was used to record the data, which were transcribed verbatim and then analysed using a step-wise phenomenographic data analysis procedure. Results: Participants reported that VMMC was implemented by the department of health with support from non-governmental organisations and private general practitioners. Negative perceptions and negative experiences regarding VMMC and implementation were reported. Conclusion: The implementation of VMMC is compromised due to poor preparation and training of healthcare workers for implementing the service. Addressing health care workers' needs for training and preparation is crucial for successful implementation of VMMC.